Managing PV power injection and storage, enabling a larger direct consumption of renewable energy: A case study for the Belgian electricity system. (31st October 2018) - Meuris, Marc; Lodewijks, Pieter; Ponnette, Raf; Meinke‐Hubeny, Frank; Valkering, Pieter; Belmans, Ronnie; Poortmans, Jef
Abstract: An overall model and scenario for increasing the share of renewable electricity consumption in the Belgium grid is proposed by simulating different PV and home battery capacities. The model is balancing the electricity generation of these renewable sources on an hourly basis with the historical consumption profiles of 2014, 2015, and 2016 to estimate how much renewable energy can be consumed directly. The model considers the problem of potential overloads on the low voltage grid, by limiting with curtailment the total PV injection on the low voltage grid to a level that can be currently sustained. A simple algorithm for grid injection limitation of this curtailment during daytime and nighttime is proposed, with and without the use of batteries. The share of renewable electricity consumption is calculated, investigating the impact of battery sizing and different levels for the power injection limit. Above a certain level, additional battery capacity has no effect. With increasing total PV deployment, the optimal power injection limit is reduced. A realistic and effective deployment scenario for renewable electricity from wind and PV is developed (up to 9 GW wind and 50 GWp PV for the Belgian case). It is possible to reach a share of consumed renewable electricity of almost 50% with a curtailment of 9% without the use of batteries. With higher PV deployment and a minimal amount of home battery capacity (1.5 kWh/kWp), a 70% share of consumed renewable energy is realized, with a curtailment of less than 20%. Abstract : Optimal grid injection limit (in kW/kWp) for a massive deployment of PV (in GWp) and battery (in kWh/kWp) secures the low voltage grid from overload at noons. Up to 70% renewable energy for electricity consumption can be realized with minimal grid upgrades.